Fetoscopic guide laser therapy for twin-twin transfusion syndrome - Yao-Lung Chang (Wolters Kluwer Medknow Publications, 2013)
Twin-twin transfusion syndrome (TTTS) affects 1 in 10 monochorionic (MC) twin pregnancies, and is the most important cause of death and neurological injuries in live-born fetuses in MC twins. Since one randomized trial demonstrated that fetoscopic laser photocoagulation achieved better outcomes than serial amniodrainage for all stages of TTTS before 26 weeks, centers of fetoscopic laser therapy for TTTS are currently being initiated worldwide. This review discusses the history, instruments and techniques of fetoscopic laser photocoagulation for TTTS. Finally, we report our current outcomes of TTTS treated by fetoscopic laser photocoagulation in a single center in Taiwan.